EMPLOYEE DISCIPLINE DEVELOPMENT STRATEGY (Study at the Head Office of Lhoksukon District, North Aceh Regency) - nurjamli jamli; Mai syuri (Jurnal Riset Akuntansi dan Manajemen Malahayati (JRAMM), 2023)
According to Law No. 43 of 1999 in article 26 states that "every Civil Servant is obliged to obey all applicable laws and regulations and carry out the official duties entrusted to him with full dedication, awareness and responsibility. The problem studied in this study is how the Strategy for Coaching Employee Discipline at the Lhoksukon Subdistrict Office, North Aceh Regency and to determine the level of employee discipline at the Cot Girek Subdistrict Office, North Aceh Regency. This study uses a qualitative approach with a descriptive style by using techniques to obtain data through observation, interviews, and documentation. The results showed that the Strategy for Coaching Employee Discipline at the District Office of Lhoksukon, North Aceh Regency, namely by evaluating employee work targets, holding coaching for all staff and employees every month, and not signing SKP (employee work targets) which are performance targets. what employees must achieve. The level of discipline of employees at the Lhoksukon sub-district office generally has the highest level of discipline with a low level of discipline as many as 48.89% (10 respondents), 40% of employees (8 respondents) have a high level of discipline and others 11.11% ( 4 respondents) have a moderate level of discipline, this happens because of intentional factors such as often being late, often absent, often not coming home yet, not wearing uniforms and neglecting superior instructions and unintentional factors such as accidents.